Поведение птенцов глухаря (Tetrao urogallus L.) при различных температурах воздуха - Волков, Н.И. (Вестник зоологии, 1970)
The younger are the nestlings of T. urogallus, the more sensitive they are to the temperature conditions of the environment in light time of the day. The night falls of temperature have no effect on nestlings. Three temperature zones are distinguished according to the nestling relation to air temperature. At the optimal temperature the nestlings have no need in heating under sitting hen; at minimum temperatures they regularly go out searching for food, but need the periodical heating under sitting hen; at extremal temperatures the nestlings avoid to leave the sitting hen. The boundaries of each temperature zone gradually change with the development of thermal regulation in birds. When nestlings are about a month the temperature conditions of the environment for them lose the primary significance.